(untitled) (Heritage, 2021)
Nostalgia is one of the basic human emotions, therefore the sentimental longing for something from the past is a feeling that most people recognize. The desire and pity for childhood is characteristic of all generations, which is why nostalgic marketing is considered a successful and valuable marketing strategy, which brings modernized versions of past objects and experiences and makes the old become new again. The main purpose of nostalgic marketing and nostalgic brands is to enable consumers to travel through time, back to early childhood and to remember their pleasant experiences and memories, and even to see themselves from a different time perspective. Such brands attract the attention of the audience by flirting with older, proven and well-known trends from the past, which evokes positive memories for consumers. This paper seeks to bring together and present information that can help companies and marketing professionals more easily decide on a nostalgic marketing strategy. Although many world-renowned companies today use nostalgic brands and nostalgic appeals to expand the target market and bridge the generation gap and beat competition in the market, the potential of this effective marketing approach is underused. For this reason, the main goal of the paper is to analyze the collected information from the available scientific literature and to offer new guidelines to experts in this field. Implementing a nostalgic marketing strategy and creating nostalgic brands creates an unbreakable emotional connection with consumers, in turn, consumers are willing to make a purchase, just to reminisce about their past memories and once again experience a sense of independence and belonging from childhood. Marketing experts would have to find a balance between the old and the new, that is, to create a modern turn towards the old product. Nostalgic brands, in today’s demanding market, should meet modern standards, but in that process of modernization they should not desecrate the basic concept with which consumers once grew up.